A review of techniques for the application of bioactive coatings on metal-based implants to achieve controlled release of active ingredients. (May 2022) - Kravanja, Katja Andrina; Finšgar, Matjaž
Graphical abstract: Highlights: A comprehensive review of various novel bioactive coating deposition techniques is presented. The application of a bioactive coating influences bone growth at the implant site and prevents post-operative complications. Different application techniques stimulate significantly different  in vitro  release rates of active ingredients. Active ingredient encapsulation is a promising method for the desired release kinetics. The common techniques for analytical determination of active ingredients are discussed. Abstract: Metallic implants have the disadvantage of being insufficiently biologically active despite their good mechanical properties and general affordability. Therefore, their bone growth at the implant site in an osteoinductive and osteoconductive manner could be improved by using bioactive coatings with incorporated active ingredients (antibiotics, anti-inflammatory drugs, growth factors, osteoclast inhibitors, anticoagulants, etc.) that are released locally at the implant site in a controlled manner. In addition, the long-term exposure of metallic implant materials to a corrosive environment (human body fluids) can lead to toxic corrosion-induced ion release. To ensure the biological, non-corrosive, and appropriate mechanical properties of the implant-coating system, the choice of the coating method is crucial. This review describes recent developments in the application of bioactive coatings on metal implant materials, such as 3D printing, electrospinning, electrophoretic deposition, dip coating, drop casting, sol–gel deposition, biomimetic deposition, plasma spraying, layer-by-layer deposition, physical vapour deposition, and the formation of titanium oxide nanotubes by anodization. In addition, this work addresses promising ways to incorporate active ingredients into coatings through various entrapment methods of nano- and micro-encapsulation to achieve the desired controlled release.